Tunable plasmon-induced transparency effect based on self-asymmetric H-shaped resonators meta-atoms. (13th February 2015) - Cheng, Zhaoxiang; Chen, Lin; Zang, Xiaofei; Cai, Bin; Peng, Yan; Zhu, Yiming
Abstract: We have proposed and demonstrated a tunable plasmon-induced transparency (PIT) effect from two ways, based on self-asymmetric H-shaped resonators (AHR) meta-atoms. The tunable PIT effect is realized via varying polarization angles and coupling distances. First, by proper design, transition from PIT mode to dipole mode is theoretically and experimentally demonstrated by simply adjusting the polarization angle. Also, the manipulation of 'dark-mode' resonance intensity from strong to weak is achieved by varying coupling strength with different distances, which provided insight into the magnetic coupling hybridization mechanism. Prospectively, due to its special tunable characteristics, the AHR meta-atoms may be widely used in slow light, filters and switch devices.